A Simple Approach for Experimental Characterization and Validation of Proton Pencil Beam Profiles - Stasica, Paulina; Baran, Jakub; Granja, Carlos; Krah, Nils; Korcyl, Grzegorz; Oancea, Cristina; Pawlik-Niedźwiecka, Monika; Niedźwiecki, Szymon; Rydygier, Marzena; Schiavi, Angelo; Rucinski, Antoni; Gajewski, Jan (Frontiers in Physics, 2020)
A precise characterization of therapeutic proton pencil beams is essential for commissioning of any treatment planning system (TPS). The dose profile characterization includes measurement of the beam lateral dose profile in the beam core and far from the beam core, in the so called low-dose envelope, and requires a sophisticated detection system with a few orders of magnitude dynamic range. We propose to use a single-quantum sensitive Minipix Timepix detector, along with an in-house designed holder to perform measurements of the pencil beam dose profile in air and in water. We validated the manufacturer calibration of the Minipix Timepix detector in proton beams of various energies and compared the deposited energy spectra to Monte Carlo (MC) simulations. The precision of the lateral dose profile measurements has been systematically validated against Krakow proton facility commissioning data and dose profile simulations performed with MC codes Gate/Geant4 and Fred. We obtained an excellent agreement between Minipix Timepix measurements and simulations demonstrating the feasibility of the system for a simple characterization and validation of proton pencil beams. The proposed approach can be implemented at any proton therapy facility to acquire experimental data needed to commission and validate analytical and MC based TPS.